The British household panel survey and its income data - Stephen P. Jenkins (University of Essex, Institute for Social and Economic Research (ISER), 2010)
This paper provides a self-contained introduction to the British Household Panel Survey (BHPS), concentrating on aspects relevant to analysis of the distribution of household income. I discuss BHPS design features and how data on net household income are derived. The BHPS net household income definition is modelled on that used in Britain's official personal income distribution statistics (Households Below Average Income, HBAI). I show that cross-sectional BHPS distributions track corresponding HBAI ones relatively well over time.
Keywords: C81; D31; I32; 330; British Household Panel Survey; household income; net income; disposable income; Households Below Average Income; income distribution; inequality; poverty; Mikrozensus; Haushaltsbudget-Statistik; Befragung; Panel; Haushaltseinkommen; Sozialstruktur; Niedrigeinkommen; Einkommensverteilung; Großbritannien